The impact of online banking on the performance of Nigerian banking sector - Musa, Auwal; Kurfi, Shafiu Abubakar; Hassan, Haslinda (2015)
In this contemporary life, information technology (IT) has become a significant medium in economic and social development.Banking sector nowadays cannot move forward rapidly without the use of IT. In particular, online banking (ebanking) is one of the IT applications with the highest impact on the global economy in creating a new business environment in the sector.Therefore, the aim of this study is to examine the impact of e-banking on the performance of the banking sector in Nigeria.E-banking will be measured by the expenditure made on information and communication technology (ICT) investments, number of debit cards issued to customers, and number of automated teller machines (ATMs) installed by the banks. Return on assets (ROA), return on equity (ROE), and net interest margin (NIM) will be used as performance variables.The impact of ebanking on the bank performance will be examined in two periods: pre-consolidation (i.e., before adopting the e-banking) and post-consolidation (i.e., after adopting the e-banking). Data collection involves secondary data gathered via annual reports of 21 Nigerian banks.The SPSS software will be used for data analysis.